SiO2@PPy / LSDW-Al photothermal absorption material and preparation method and application thereof
Patent Information
- Application Number
- CN202311101812.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-08-29
AI Technical Summary
In existing interface-type solar evaporators, the disordered pore structure and poor thermal conductivity of unstructured capillary materials hinder evaporator optimization, resulting in a decreased evaporation rate and inefficient heat utilization.
Using aluminum sheets as a substrate, an ordered mesh-like microstructure is formed by laser etching. Combined with polypyrrole and silicon dioxide layers, SiO2@PPy/LSDW-Al photothermal absorbing material is prepared for use in an interfacial evaporator to achieve efficient water evaporation.
It improves evaporation rate and heat utilization efficiency, reduces heat loss, has excellent photothermal conversion capability and salt resistance, and is suitable for seawater desalination.
Smart Images

Figure CN117146451B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solar interface evaporator technology, specifically to a SiO2@PPy / LSDW-Al photothermal absorbing material, its preparation method, and its application. Background Technology
[0002] To address the problem of freshwater scarcity, various advanced seawater desalination technologies have been developed, such as reverse osmosis, multi-stage flash distillation, multi-effect distillation, and steam compression distillation. However, conventional seawater desalination technologies not only require complex and expensive infrastructure but also consume large amounts of fossil fuels. Furthermore, people are unwilling to obtain freshwater at the expense of environmental pollution. Therefore, developing a new generation of low-cost, sustainable, portable, and efficient desalination technologies is crucial to meeting the freshwater needs of various regions.
[0003] As the largest green energy source on Earth, and inspired by natural evaporation, solar energy has become a popular choice for solving the problem of freshwater scarcity by driving the evaporation of seawater surface. Interfacial solar evaporators typically use unstructured capillary materials, such as paper, commercial textiles, porous carbon, and polymers, as carriers for photothermal absorbers for water evaporation. However, the disordered pore structure and inherent limitations of these materials hinder the optimization of evaporators: (1) The disordered pore structure is not conducive to the heat and mass transfer process during evaporation, leading to salt accumulation on the evaporator surface, blockage of water supply pipes, and uneven heat utilization, which reduces the evaporation rate. (2) The extremely low thermal conductivity of these materials introduces high thermal resistance, which has an adverse effect on the overall performance of the evaporator. Summary of the Invention
[0004] To address the problem that the disordered pore structure of unstructured capillary materials in existing interfacial solar evaporators hinders evaporator optimization due to their inherent limitations, this invention provides a SiO2@PPy / LSDW-Al photothermal absorbing material, its preparation method, and its application. Using a thermally conductive aluminum sheet as a substrate, an ordered mesh-like microstructure with adjustable shape and size is prepared on the aluminum sheet, thereby obtaining the SiO2@PPy / LSDW-Al photothermal absorbing material. Applying this SiO2@PPy / LSDW-Al photothermal absorbing material to an interfacial evaporator enables efficient interfacial water evaporation.
[0005] To achieve the above objectives, the present invention provides the following technical solution: a SiO2@PPy / LSDW-Al photothermal absorbing material, comprising an aluminum sheet with a mesh-like microstructure on one side, a polypyrrole layer bonded to the surface of the mesh-like microstructure on the aluminum sheet, and a silicon dioxide layer loaded on the polypyrrole layer, wherein the mesh-like microstructure is composed of multiple interlaced grooves with equal horizontal and vertical spacing etched by laser, the line spacing of the horizontal and vertical grooves is 0.04-0.18 mm, the width is 0.05 mm, and the depth is 80 μm-180 μm.
[0006] Furthermore, the size of the mesh microtexture is the same as that of the aluminum sheet, and the total thickness of the mesh microtexture, the polypyrrole layer, and the silicon dioxide layer does not exceed 160 μm.
[0007] Furthermore, the Si atom content in the SiO2@PPy / LSDW-Al photothermal absorbing material is 0.6%-3%.
[0008] This invention provides a method for preparing SiO2@PPy / LSDW-Al photothermal absorbing material, the specific steps of which are as follows:
[0009] S1 performs single-sided laser etching on an aluminum sheet to form a mesh-like microstructure on the surface of the aluminum sheet, thus obtaining a laser-processed aluminum sheet;
[0010] S2 immerses a laser-processed aluminum sheet in a pyrrole solution at 2℃-4℃ to obtain a laser-processed aluminum sheet with pyrrole deposition;
[0011] S3 immersed the laser-processed aluminum sheet with pyrrole deposition in a mixed solution of iodine and n-hexane at a temperature of -14°C to -5°C, and then dried to obtain a laser-processed aluminum sheet loaded with polypyrrole.
[0012] S4 sputters silicon dioxide onto the surface of a laser-processed aluminum sheet loaded with polypyrrole to obtain a laser-processed aluminum sheet loaded with silicon dioxide and polypyrrole, namely SiO2@PPy-LSDW-Al photothermal absorbing material.
[0013] Furthermore, in S1, the parameters for single-sided laser etching are set as follows: the laser beam is perpendicularly irradiated on the surface of the aluminum sheet, the power is 20W-30W, the scanning speed is 60mm / s-90mm / s, the line spacing is 0.04mm-0.18mm, the frequency is 20KHz-60KHz, the scanning path is longitudinal and transverse scanning, the angle is 0° and 270°, and the scanning is repeated 1 to 3 times.
[0014] Furthermore, in S2, the laser-processed aluminum sheet is immersed in a pyrrole solution for 6-12 hours.
[0015] Furthermore, in S3, the laser-processed aluminum sheet with pyrrole deposition is immersed in a mixed solution of iodine and n-hexane with a concentration of 0.006 mmol / ml-0.095 mmol / ml for 12 h-48 h, and then dried at 60 °C-90 °C for 6 h-24 h.
[0016] Furthermore, in S4, the sputtered silicon dioxide uses a SiO2 target with a purity of 99.9%. The specific sputtering process is as follows: sputtering for 5 min to 40 min under an argon gas flow and a power of 150 W to 200 W, followed by sputtering for 3 min to 10 min under a mixed argon and oxygen gas flow and a power of 150 W to 200 W.
[0017] The present invention provides an interface evaporator comprising polystyrene foam, and the above-mentioned SiO2@PPy / LSDW-Al photothermal absorbing material or SiO2@PPy / LSDW-Al photothermal absorbing material prepared by the above preparation method disposed on the polystyrene foam.
[0018] Furthermore, the SiO2@PPy / LSDW-Al photothermal absorbing material has a supply end and a drainage end connected to its mesh microstructure. The supply end is located on both sides of the evaporator and its width accounts for 80% of the corresponding side length. The drainage end is located on the other two sides of the evaporator and its width accounts for 20% of the corresponding side length. The length of the drainage end is greater than the length of the supply end.
[0019] Compared with the prior art, the present invention has at least the following beneficial effects:
[0020] This invention provides a SiO2@PPy / LSDW-Al photothermal absorbing material with an aluminum sheet as the substrate. The high thermal conductivity of aluminum avoids the adverse effects of thermal resistance, reduces heat loss, and is beneficial to improving the evaporation rate. The prepared photothermal absorbing material has a three-level structure, including a mesh microstructure with adjustable size obtained by laser single-sided processing on the aluminum sheet. The bottom groove of the first-level mesh microstructure is used for water transport. The etched porous skeleton of the second-level intermediate layer has a capillary effect to draw water from the bottom layer to the photothermal evaporation surface and also provides sites for subsequent loading of polypyrrole (PPy) and silicon dioxide (SiO2). The top SiO2@PPy / photothermal film of the third level is used for photothermal conversion and positioning the heated water to achieve evaporation, which can realize efficient photothermal conversion.
[0021] The photothermal absorbing material of this invention is very thin. Only a 160μm water film needs to be heated at the photothermal evaporation interface. Compared with the traditional water channel with the same height as the overall material (generally greater than 1cm), the conduction loss can be greatly reduced, and there is no need to worry about heat loss caused by heating the overall evaporation device. This is beneficial to improving the evaporation rate and efficiency.
[0022] This invention provides a method for preparing SiO2@PPy / LSDW-Al photothermal absorbing material. Using an aluminum sheet as the substrate, the high thermal conductivity of aluminum avoids the adverse effects of thermal resistance and is beneficial for increasing the evaporation rate. One side of the aluminum sheet is laser-treated to obtain a mesh-like microstructure, providing sites for subsequent loading of polypyrrole (PPy) and silicon dioxide (SiO2). A mixed solution of iodine and n-hexane is used as an oxidant, which promotes the growth of PPy at low temperatures, enabling efficient photothermal conversion. Furthermore, a SiO2 target is sputtered onto PPy-LSDW-Al to form a SiO2 layer of a certain thickness. SiO2 can act as an antireflective layer, facilitating more efficient light absorption by polypyrrole, and also as an insulating layer, reducing convection losses between the photothermal material and air, thus promoting photothermal conversion and concentrated heat utilization.
[0023] This invention utilizes SiO2@PPy / LSDW-Al photothermal absorbing material in the preparation of an interfacial evaporator. The resulting interfacial photothermal evaporator is a metal-based capillary material with a controllable structure. Combined with excellent photothermal conversion capability and a reasonable flow guide design, it can efficiently evaporate interfacial water. Thanks to the excellent photothermal conversion capability, superior heat and mass transfer capability, low heat loss rate, and reasonable flow guide method of SiO2@PPy / LSDW-Al, no salt accumulation occurs even after long-term use, and it also exhibits excellent salt resistance when processing high-salinity solutions. Therefore, the interfacial evaporator of this invention can be applied to seawater desalination. Attached Figure Description
[0024] Figure 1 This is a schematic diagram of a traditional interfacial evaporator and the induced flow interfacial evaporator in this invention.
[0025] Figure 2 The images show the morphology of laser-processed aluminum sheets loaded with SiO2@PPy at various stages. A1-3 are the morphology images of LSDW-Al at scales of 200μm, 20μm, and 2μm, respectively. B1-3 are the morphology images of PPy-LSDW-Al at scales of 200μm, 20μm, and 2μm, respectively. C1-3 are the morphology images of SiO2@PPy-LSDW-Al at scales of 200μm, 20μm, and 2μm, respectively.
[0026] Figure 3 The light absorption diagrams are for Al, LSDW-Al, and SiO2@PPy-LSDW-Al.
[0027] Figure 4 The image shows the photothermal conversion of SiO2@PPy-LSDW-Al under one simulated solar illumination.
[0028] Figure 5The figure shows the mass loss of LSDW-Al, SiO2@PPy-LSDW-Al and SiO2@PPy-LSDW-Al-guided interface evaporators under one solar simulated illumination. Detailed Implementation
[0029] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.
[0030] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0031] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0032] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0033] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”
[0034] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0035] This invention provides a flexible liquid diode evaporator based on copper hydroxide, its preparation method, and its application.
[0036] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0037] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.
[0038] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.
[0039] This invention discloses a method for preparing SiO2@PPy-LSDW-Al photothermal absorbing material, the specific steps of which are as follows:
[0040] (1) First, cut the aluminum sheet into the required size (e.g., 3*3cm), then soak it in anhydrous ethanol and sonicate it for 30 minutes. Finally, blow it dry with nitrogen to obtain a clean aluminum sheet.
[0041] (2) In an air environment, a laser marking machine (LG-20) is used to perform single-sided processing to etch multiple grooves with equal horizontal and vertical spacing on the aluminum sheet, forming a mesh micro-texture on the surface of the aluminum sheet, thus obtaining a laser-processed aluminum sheet (LSDW-Al). The mesh aperture of this mesh micro-texture is adjustable.
[0042] Preferably, the spacing between the horizontal and vertical grooves is 0.04-0.18 mm, the width is 0.05 mm, and the depth is 80 μm-180 μm.
[0043] Preferably, the mesh openings of the mesh microstructure are square with a side length of 0.04-0.18 mm;
[0044] Preferably, the size of the mesh microtexture is the same as the size of the aluminum sheet to be processed;
[0045] Preferably, the laser marking machine parameters are set as follows: the laser beam is vertically irradiated on the substrate surface, the laser power is 20-30W, the scanning speed is 60-90mm / s, the line spacing is 0.04-0.18mm, the frequency is 20-60KHz, the scanning path is longitudinal and transverse scanning (angles are 0° and 270°), and the scanning is repeated 1 to 3 times.
[0046] (3) At 2-4℃, LSDW-Al is soaked in pyrrole (Py) solution for 6-12h to allow the microstructure of LSDW-Al to fully contact with pyrrole. Pyrrole can wet and coat the surface of the microstructure, and then polypyrrole can be polymerized and grown on the surface of the microstructure to obtain laser-processed aluminum sheet (Py-LSDW-Al) with pyrrole deposition.
[0047] Preferably, the pyrrole solution is a commercially available analytical grade pyrrole solution.
[0048] (4) At room temperature, prepare a mixed solution of iodine and n-hexane with a concentration of 0.006-0.095 mmol / ml, stir and sonicate for 1 h to completely dissolve the iodine and obtain a homogeneous mixed solution. Immerse Py-LSDW-Al in the mixed solution of iodine and n-hexane at -14℃ to -5℃ for 12-48 h. Pyrrole polymerizes and grows into polypyrrole PPy under the oxidation of iodine. Then, dry it in an oven at 60-90℃ for 6-24 h. This removes residual iodine and n-hexane and allows polypyrrole to adhere to the microstructure surface of LSDW-Al. Afterward, rinse with anhydrous ethanol to remove residual iodine and dry at room temperature to obtain a laser-processed aluminum sheet (PPy-LSDW-Al) loaded with polypyrrole.
[0049] Specifically, rinsing with anhydrous ethanol yields a yellow waste liquid, indicating that polypyrrole is firmly bonded to the microstructure surface of LSDW-Al, while obtaining a dark green waste liquid indicates that further heating and drying are required to obtain PPy-LSDW-Al.
[0050] (6) Place PPy-LSDW-Al into the magnetron sputtering system.
[0051] Using an RF power source as the sputtering source, the vacuum in the sputtering chamber was evacuated to 1.9 × 10⁻⁶ using a mechanical pump and a molecular pump in sequence. - 3 Pa, then argon gas (50 sccm), and adjust the pressure of the vacuum chamber to 0.6 Pa.
[0052] The sputtering process uses a high-purity SiO2 target (99.9%), and pre-sputtering for 3 minutes before sputtering is performed to remove impurities from the target surface.
[0053] The material was first sputtered under an argon gas flow at a power of 150-200W for 5-40 minutes, followed by sputtering under a mixed argon and oxygen (20 sccm) gas flow at a power of 150-200W for 3-10 minutes. This yielded a laser-processed aluminum sheet loaded with silica and polypyrrole, namely SiO2@PPy-LSDW-Al photothermal absorbing material.
[0054] EDS analysis revealed that the Si atom content in the laser-processed aluminum sheet loaded with silica and polypyrrole was between 0.6% and 3%.
[0055] This invention also provides an interfacial evaporator, prepared using the aforementioned SiO2@PPy-LSDW-Al photothermal absorbing material, specifically:
[0056] Polystyrene foam was cut into circles with a diameter of 8 cm. The obtained SiO2@PPy-LSDW-Al photothermal absorbing material was placed on the polystyrene foam, with the mesh microstructure of the SiO2@PPy-LSDW-Al photothermal absorbing material facing away from the polystyrene foam.
[0057] The SiO2@PPy-LSDW-Al photothermal absorber material has a mesh-like microstructure with a supply end and a drainage end connected together, with a connection width of approximately 2-3 mm. Paper towels, absorbent cotton, filter paper, and commercial textiles are used as the supply end for bulk water and the drainage end for concentrated water. The supply end is located on both sides of the evaporator and its width accounts for 80% of the corresponding side length. The drainage end is located on the other two sides and its width accounts for 20% of the corresponding side length. The length of the drainage end is greater than the length of the supply end to form a siphon effect. Evaporation performance tests are then conducted.
[0058] Example 1
[0059] 1. Preparation of SiO2@PPy / LSDW-Al photothermal absorbing material
[0060] (1) First, cut the aluminum sheet into the required size (e.g., 3*3cm), then soak it in anhydrous ethanol and sonicate it for 30 minutes. Finally, blow it dry with nitrogen to obtain a clean aluminum sheet.
[0061] (2) In an air environment, a laser marking machine (LG-20) is used to perform single-sided processing to etch an adjustable mesh microtexture surface consisting of grooves with a line spacing of 0.04 mm, a width of 0.05 mm, and a depth of 80 μm, to obtain a laser-processed aluminum sheet (LSDW-Al).
[0062] The laser parameters are set as follows: the laser beam is perpendicular to the substrate surface, the laser power is 20, the scanning speed is 90 mm / s, the line spacing is 0.04 mm, the frequency is 60 kHz, the scanning path is longitudinal and transverse scanning (angles are 0° and 270°), and the scanning is repeated once.
[0063] (3) At 2℃, LSDW-Al was soaked in pyrrole (Py) solution for 6h to allow the microstructure of LSDW-Al to fully contact with pyrrole and allow pyrrole to be fully adsorbed on the microstructure of LSDW-Al, thus obtaining laser-processed aluminum sheet (Py-LSDW-Al) with pyrrole deposition.
[0064] (4) At room temperature, a mixed solution of iodine and n-hexane with a concentration of 0.006 mmol / ml was prepared, stirred, and sonicated for 1 h to completely dissolve the iodine and obtain a homogeneous mixed solution. LSDW-Al, which was in full contact with pyrrole, was immersed in the mixed solution of iodine and n-hexane at -5°C for 12 h, and then dried in an oven at 60°C for 6 h to allow polypyrrole to adhere to the microstructure surface of LSDW-Al. Afterwards, residual iodine was removed by rinsing with anhydrous ethanol and dried at room temperature to obtain a laser-processed aluminum sheet loaded with polypyrrole (PPy-LSDW-Al).
[0065] (6) Place the PPy-LSDW-Al into the magnetron sputtering system. Using an RF power supply as the sputtering source, evacuate the sputtering chamber to 1.9 × 10⁻⁶ vacuum using a mechanical pump and a molecular pump in sequence. -3 Pa, then argon gas (50 sccm), and adjust the pressure of the vacuum chamber to 0.6 Pa.
[0066] The sputtering process uses a high-purity SiO2 target (99.9%), and pre-sputtering for 3 minutes before sputtering is performed to remove impurities from the target surface.
[0067] Then, the material was sputtered for 40 minutes under an argon gas flow and a power of 150W, followed by sputtering for 10 minutes under a mixed argon and oxygen (20 sccm) gas flow and a power of 150W, to obtain SiO2@PPy-LSDW-Al photothermal absorbing material.
[0068] 2. Assemble the evaporator
[0069] Polystyrene foam was cut into circles with a diameter of 8 cm, and the obtained SiO2@PPy-LSDW-Al photothermal absorbing material was placed on the polystyrene foam. Paper towels, absorbent cotton, filter paper, and commercial textiles were used as the supply end for bulk water and the drainage end for concentrated water. The supply end was located on both sides of the evaporator, with a width occupying 80% of the corresponding side length. The drainage ends were located on the other two sides, with a width occupying 20% of the corresponding side length, and the length of the drainage ends was greater than the length of the supply end. Evaporation performance was then tested, and the evaporation rate was 1.8 kg / m³. -2 h -1 .
[0070] Example 2
[0071] 1. Preparation of SiO2@PPy / LSDW-Al photothermal absorbing material
[0072] (1) First, cut the aluminum sheet into the required size (e.g., 3*3cm), then soak it in anhydrous ethanol and sonicate it for 30 minutes. Finally, blow it dry with nitrogen to obtain a clean aluminum sheet.
[0073] (2) In an air environment, a laser marking machine (LG-20) is used to perform single-sided processing to etch an adjustable mesh microtexture surface consisting of grooves with a line spacing of 0.18 mm, a width of 0.05 mm, and a depth of 80 μm, to obtain a laser-processed aluminum sheet (LSDW-Al).
[0074] The laser parameters are set as follows: the laser beam is perpendicular to the substrate surface, the laser power is 20, the scanning speed is 90 mm / s, the line spacing is 0.18 mm, the frequency is 60 kHz, the scanning path is longitudinal and transverse scanning (angles are 0° and 270°), and the scanning is repeated once.
[0075] (3) At 2℃, LSDW-Al was soaked in pyrrole (Py) solution for 12h to allow the microstructure of LSDW-Al to fully contact with pyrrole and allow pyrrole to be fully adsorbed on the microstructure of LSDW-Al, thus obtaining laser-processed aluminum sheet (Py-LSDW-Al) with pyrrole deposition.
[0076] (4) At room temperature, a mixed solution of iodine and n-hexane with a concentration of 0.012 mmol / ml was prepared, stirred, and sonicated for 1 h to completely dissolve the iodine and obtain a homogeneous mixed solution. LSDW-Al, which was in full contact with pyrrole, was immersed in the mixed solution of iodine and n-hexane at -14°C for 24 h, and then dried in a 90°C oven for 12 h to allow polypyrrole to adhere to the microstructure surface of LSDW-Al. Afterwards, residual iodine was removed by rinsing with anhydrous ethanol and dried at room temperature to obtain a laser-processed aluminum sheet loaded with polypyrrole (PPy-LSDW-Al).
[0077] (6) Place the PPy-LSDW-Al into the magnetron sputtering system. Using an RF power supply as the sputtering source, evacuate the sputtering chamber to 1.9 × 10⁻⁶ vacuum using a mechanical pump and a molecular pump in sequence. -3 Pa, then argon gas (50 sccm), and adjust the pressure of the vacuum chamber to 0.6 Pa.
[0078] The sputtering process uses a high-purity SiO2 target (99.9%), and pre-sputtering for 3 minutes before sputtering is performed to remove impurities from the target surface.
[0079] Then, the material was sputtered for 20 minutes under an argon gas flow and a power of 200W, followed by sputtering for 5 minutes under a mixed argon and oxygen gas flow (20 sccm) and a power of 200W, to obtain SiO2@PPy-LSDW-Al photothermal absorbing material.
[0080] 2. Assemble the evaporator
[0081] Polystyrene foam was cut into circles with a diameter of 8 cm, and the obtained SiO2@PPy-LSDW-Al photothermal absorbing material was placed on the polystyrene foam. Paper towels, absorbent cotton, filter paper, and commercial textiles were used as the supply end for bulk water and the drainage end for concentrated water. The supply end was located on both sides of the evaporator, with a width occupying 80% of the corresponding side length. The drainage ends were located on the other two sides, with a width occupying 20% of the corresponding side length, and the length of the drainage ends was greater than the length of the supply end. Evaporation performance was then tested, and the evaporation rate was 2.2 kg / m³. -2 h -1 .
[0082] Example 3
[0083] 1. Preparation of SiO2@PPy / LSDW-Al photothermal absorbing material
[0084] (1) First, cut the aluminum sheet into the required size (e.g., 3*3cm), then soak it in anhydrous ethanol and sonicate it for 30 minutes. Finally, blow it dry with nitrogen to obtain a clean aluminum sheet.
[0085] (2) In an air environment, a laser marking machine (LG-20) is used to perform single-sided processing to etch an adjustable mesh microtexture surface consisting of grooves with a line spacing of 0.15 mm, a width of 0.05 mm, and a depth of 100 μm, to obtain a laser-processed aluminum sheet (LSDW-Al).
[0086] The laser parameters are set as follows: the laser beam is perpendicular to the substrate surface, the laser power is 30W, the scanning speed is 90mm / s, the line spacing is 0.15mm, the frequency is 30KHz, the scanning path is longitudinal and transverse scanning (angles are 0° and 270°), and the scanning is repeated 3 times.
[0087] (3) At 4℃, LSDW-Al was soaked in pyrrole (Py) solution for 6 hours to allow the microstructure of LSDW-Al to fully contact with pyrrole and allow pyrrole to be fully adsorbed on the microstructure of LSDW-Al, thus obtaining laser-processed aluminum sheet with pyrrole deposition (Py-LSDW-Al).
[0088] (4) At room temperature, a mixed solution of iodine and n-hexane with a concentration of 0.048 mmol / ml was prepared, stirred, and sonicated for 1 h to completely dissolve the iodine and obtain a homogeneous mixed solution. LSDW-Al, which was in full contact with pyrrole, was immersed in the mixed solution of iodine and n-hexane at -14°C for 48 h, and then dried in an oven at 60°C for 8 h to allow polypyrrole to adhere to the microstructure surface of LSDW-Al. Afterwards, residual iodine was removed by rinsing with anhydrous ethanol and dried at room temperature to obtain a laser-processed aluminum sheet loaded with polypyrrole (PPy-LSDW-Al).
[0089] (6) Place the PPy-LSDW-Al into the magnetron sputtering system. Using an RF power supply as the sputtering source, evacuate the sputtering chamber to 1.9 × 10⁻⁶ vacuum using a mechanical pump and a molecular pump in sequence. -3 Pa, then argon gas (50 sccm), and adjust the pressure of the vacuum chamber to 0.6 Pa.
[0090] The sputtering process uses a high-purity SiO2 target (99.9%), and pre-sputtering for 3 minutes before sputtering is performed to remove impurities from the target surface.
[0091] Then, the material was sputtered for 40 minutes under an argon gas flow and a power of 150W, followed by sputtering for 10 minutes under a mixed argon and oxygen (20 sccm) gas flow and a power of 150W, to obtain SiO2@PPy-LSDW-Al photothermal absorbing material.
[0092] 2. Assemble the evaporator
[0093] Polystyrene foam was cut into circles with a diameter of 8 cm, and the obtained SiO2@PPy-LSDW-Al photothermal absorbing material was placed on the polystyrene foam. Paper towels, absorbent cotton, filter paper, and commercial textiles were used as the supply end for bulk water and the drainage end for concentrated water. The supply end was located on both sides of the evaporator, with a width occupying 80% of the corresponding side length. The drainage ends were located on the other two sides, with a width occupying 20% of the corresponding side length, and the length of the drainage ends was greater than the length of the supply end. Evaporation performance was then tested, and the evaporation rate was 1.6 kg / m³. -2 h -1 .
[0094] Example 4
[0095] 1. Preparation of SiO2@PPy / LSDW-Al photothermal absorbing material
[0096] (1) First, cut the aluminum sheet into the required size (e.g., 3*3cm), then soak it in anhydrous ethanol and sonicate it for 30 minutes. Finally, blow it dry with nitrogen to obtain a clean aluminum sheet.
[0097] (2) In an air environment, a laser marking machine (LG-20) is used to perform single-sided processing to etch an adjustable mesh microtexture surface consisting of grooves with a line spacing of 0.15 mm, a width of 0.05 mm, and a depth of 100 μm, to obtain a laser-processed aluminum sheet (LSDW-Al).
[0098] The laser parameters are set as follows: the laser beam is perpendicular to the substrate surface, the laser power is 30W, the scanning speed is 90mm / s, the line spacing is 0.15mm, the frequency is 30KHz, the scanning path is longitudinal and transverse scanning (angles are 0° and 270°), and the scanning is repeated 3 times.
[0099] (3) At 4℃, LSDW-Al was soaked in pyrrole (Py) solution for 6 hours to allow the microstructure of LSDW-Al to fully contact with pyrrole and allow pyrrole to be fully adsorbed on the microstructure of LSDW-Al, thus obtaining laser-processed aluminum sheet with pyrrole deposition (Py-LSDW-Al).
[0100] (4) At room temperature, a mixed solution of iodine and n-hexane with a concentration of 0.095 mmol / ml was prepared, stirred, and sonicated for 1 h to completely dissolve the iodine and obtain a homogeneous mixed solution. LSDW-Al, which was in full contact with pyrrole, was immersed in the mixed solution of iodine and n-hexane at -14 °C for 36 h, and then dried in an oven at 60 °C for 8 h to allow polypyrrole to adhere to the microstructure surface of LSDW-Al. Afterwards, residual iodine was removed by rinsing with anhydrous ethanol and dried at room temperature to obtain a laser-processed aluminum sheet (PPy-LSDW-Al) loaded with polypyrrole.
[0101] (6) Place the PPy-LSDW-Al into the magnetron sputtering system. Using an RF power supply as the sputtering source, evacuate the sputtering chamber to 1.9 × 10⁻⁶ vacuum using a mechanical pump and a molecular pump in sequence. -3 Pa, then argon gas (50 sccm), and adjust the pressure of the vacuum chamber to 0.6 Pa.
[0102] The sputtering process uses a high-purity SiO2 target (99.9%), and pre-sputtering for 3 minutes before sputtering is performed to remove impurities from the target surface.
[0103] Then, the material was sputtered for 40 minutes under an argon gas flow and a power of 200W, followed by sputtering for 10 minutes under a mixed argon and oxygen (20 sccm) gas flow and a power of 200W, to obtain SiO2@PPy-LSDW-Al photothermal absorbing material.
[0104] 2. Assemble the evaporator
[0105] Polystyrene foam was cut into circles with a diameter of 8 cm, and the obtained SiO2@PPy-LSDW-Al photothermal absorbing material was placed on the polystyrene foam. Paper towels, absorbent cotton, filter paper, and commercial textiles were used as the supply end for bulk water and the drainage end for concentrated water. The supply end was located on both sides of the evaporator, with a width occupying 80% of the corresponding side length. The drainage ends were located on the other two sides, with a width occupying 20% of the corresponding side length, and the length of the drainage ends was greater than the length of the supply end. Evaporation performance was then tested, and the evaporation rate was 1.9 kg m³. -2 h -1 .
[0106] Example 5
[0107] 1. Preparation of SiO2@PPy / LSDW-Al photothermal absorbing material
[0108] (1) First, cut the aluminum sheet into the required size (e.g., 3*3cm), then soak it in anhydrous ethanol and sonicate it for 30 minutes. Finally, blow it dry with nitrogen to obtain a clean aluminum sheet.
[0109] (2) In an air environment, a laser marking machine (LG-20) is used to perform single-sided processing to etch an adjustable mesh microtexture surface consisting of grooves with a line spacing of 0.15 mm, a width of 0.05 mm, and a depth of 160 μm, to obtain a laser-processed aluminum sheet (LSDW-Al).
[0110] The laser parameters were set as follows: the laser beam was perpendicularly irradiated onto the substrate surface, the laser power was 30W, the scanning speed was 60mm / s, the line spacing was 0.15mm, the frequency was 30KHz, the scanning path was longitudinal and transverse scanning (angles of 0° and 270°), and the scanning was repeated 3 times.
[0111] (3) At 4℃, LSDW-Al was soaked in pyrrole (Py) solution for 6 hours to allow the microstructure of LSDW-Al to fully contact with pyrrole and allow pyrrole to be fully adsorbed on the microstructure of LSDW-Al, thus obtaining laser-processed aluminum sheet with pyrrole deposition (Py-LSDW-Al).
[0112] (4) At room temperature, a mixed solution of iodine and n-hexane with a concentration of 0.012 mmol / ml was prepared, stirred, and sonicated for 1 h to completely dissolve the iodine and obtain a homogeneous mixed solution. LSDW-Al, which was in full contact with pyrrole, was immersed in the mixed solution of iodine and n-hexane at -10 °C for 48 h, and then dried in an oven at 60 °C for 8 h to allow polypyrrole to adhere to the microstructure surface of LSDW-Al. Afterwards, residual iodine was removed by rinsing with anhydrous ethanol and dried at room temperature to obtain a laser-processed aluminum sheet (PPy-LSDW-Al) loaded with polypyrrole.
[0113] (6) Place the PPy-LSDW-Al into the magnetron sputtering system. Using an RF power supply as the sputtering source, evacuate the sputtering chamber to 1.9 × 10⁻⁶ vacuum using a mechanical pump and a molecular pump in sequence. -3 Pa, then argon gas (50 sccm), and adjust the pressure of the vacuum chamber to 0.6 Pa.
[0114] The sputtering process uses a high-purity SiO2 target (99.9%), and pre-sputtering for 3 minutes before sputtering is performed to remove impurities from the target surface.
[0115] Then, the material was sputtered for 5 minutes under an argon gas flow and a power of 150W, followed by sputtering for 3 minutes under a mixed argon and oxygen (20 sccm) gas flow and a power of 150W, to obtain SiO2@PPy-LSDW-Al photothermal absorbing material.
[0116] 2. Assemble the evaporator
[0117] Polystyrene foam was cut into circles with a diameter of 8 cm, and the obtained SiO2@PPy-LSDW-Al photothermal absorbing material was placed on the polystyrene foam. Paper towels, absorbent cotton, filter paper, and commercial textiles were used as the supply end for bulk water and the drainage end for concentrated water. The supply end was located on both sides of the evaporator, with a width occupying 80% of the corresponding side length. The drainage ends were located on the other two sides, with a width occupying 20% of the corresponding side length, and the length of the drainage ends was greater than the length of the supply end. Evaporation performance was then tested, and the evaporation rate was 3.2 kg / m³. -2 h -1 .
[0118] Example 6
[0119] 1. Preparation of SiO2@PPy / LSDW-Al photothermal absorbing material
[0120] (1) First, cut the aluminum sheet into the required size (e.g., 3*3cm), then soak it in anhydrous ethanol and sonicate it for 30 minutes. Finally, blow it dry with nitrogen to obtain a clean aluminum sheet.
[0121] (2) In an air environment, a laser marking machine (LG-20) is used to perform single-sided processing to etch an adjustable mesh microtexture surface consisting of grooves with a line spacing of 0.15 mm, a width of 0.05 mm, and a depth of 170 μm, to obtain a laser-processed aluminum sheet (LSDW-Al).
[0122] The laser parameters are set as follows: the laser beam is perpendicular to the substrate surface, the laser power is 25W, the scanning speed is 80mm / s, the line spacing is 0.15mm, the frequency is 20KHz, the scanning path is longitudinal and transverse scanning (angles are 0° and 270°), and the scanning is repeated 3 times.
[0123] (3) At 4℃, LSDW-Al was soaked in pyrrole (Py) solution for 10h to allow the microstructure of LSDW-Al to fully contact with pyrrole and allow pyrrole to be fully adsorbed on the microstructure of LSDW-Al, thus obtaining laser-processed aluminum sheet with pyrrole deposition (Py-LSDW-Al).
[0124] (4) At room temperature, a mixed solution of iodine and n-hexane with a concentration of 0.036 mmol / ml was prepared, stirred, and sonicated for 1 h to completely dissolve the iodine and obtain a homogeneous mixed solution. LSDW-Al, which was in full contact with pyrrole, was immersed in the mixed solution of iodine and n-hexane at -10°C for 36 h, and then dried in an oven at 60°C for 24 h to allow polypyrrole to adhere to the microstructure surface of LSDW-Al. Afterwards, residual iodine was removed by rinsing with anhydrous ethanol and dried at room temperature to obtain a laser-processed aluminum sheet loaded with polypyrrole (PPy-LSDW-Al).
[0125] (6) Place the PPy-LSDW-Al into the magnetron sputtering system. Using an RF power supply as the sputtering source, evacuate the sputtering chamber to 1.9 × 10⁻⁶ vacuum using a mechanical pump and a molecular pump in sequence. -3 Pa, then argon gas (50 sccm), and adjust the pressure of the vacuum chamber to 0.6 Pa.
[0126] The sputtering process uses a high-purity SiO2 target (99.9%), and pre-sputtering for 3 minutes before sputtering is performed to remove impurities from the target surface.
[0127] Then, the material was sputtered for 5 minutes under an argon gas flow and a power of 180W, followed by sputtering for 3 minutes under a mixed argon and oxygen (20 sccm) gas flow and a power of 180W, to obtain SiO2@PPy-LSDW-Al photothermal absorbing material.
[0128] 2. Assemble the evaporator
[0129] Polystyrene foam was cut into circles with a diameter of 8 cm, and the obtained SiO2@PPy-LSDW-Al photothermal absorbing material was placed on the polystyrene foam. Paper towels, absorbent cotton, filter paper, and commercial textiles were used as the supply end for bulk water and the drainage end for concentrated water. The supply end was located on both sides of the evaporator, with a width occupying 80% of the corresponding side length. The drainage ends were located on the other two sides, with a width occupying 20% of the corresponding side length, and the length of the drainage ends was greater than the length of the supply end. Evaporation performance was then tested, and the evaporation rate was 3.5 kg / m³. -2 h -1 .
[0130] Example 7
[0131] 1. Preparation of SiO2@PPy / LSDW-Al photothermal absorbing material
[0132] (1) First, cut the aluminum sheet into the required size (e.g., 3*3cm), then soak it in anhydrous ethanol and sonicate it for 30 minutes. Finally, blow it dry with nitrogen to obtain a clean aluminum sheet.
[0133] (2) In an air environment, a laser marking machine (LG-20) is used to perform single-sided processing to etch an adjustable mesh microtexture surface consisting of grooves with a line spacing of 0.15 mm, a width of 0.05 mm, and a depth of 100 μm, to obtain a laser-processed aluminum sheet (LSDW-Al).
[0134] The laser parameters are set as follows: the laser beam is perpendicular to the substrate surface, the laser power is 30W, the scanning speed is 90mm / s, the line spacing is 0.15mm, the frequency is 30KHz, the scanning path is longitudinal and transverse scanning (angles are 0° and 270°), and the scanning is repeated twice.
[0135] (3) At 4℃, LSDW-Al was soaked in pyrrole (Py) solution for 12h to allow the microstructure of LSDW-Al to fully contact with pyrrole and allow pyrrole to be fully adsorbed on the microstructure of LSDW-Al, thus obtaining laser-processed aluminum sheet with pyrrole deposition (Py-LSDW-Al).
[0136] (4) At room temperature, a mixed solution of iodine and n-hexane with a concentration of 0.024 mmol / ml was prepared, stirred, and sonicated for 1 h to completely dissolve the iodine and obtain a homogeneous mixed solution. LSDW-Al, which was in full contact with pyrrole, was immersed in the mixed solution of iodine and n-hexane at -10 °C for 36 h, and then dried in an oven at 60 °C for 8 h to allow polypyrrole to adhere to the microstructure surface of LSDW-Al. Afterwards, residual iodine was removed by rinsing with anhydrous ethanol and dried at room temperature to obtain a laser-processed aluminum sheet loaded with polypyrrole (PPy-LSDW-Al).
[0137] (6) Place the PPy-LSDW-Al into the magnetron sputtering system. Using an RF power supply as the sputtering source, evacuate the sputtering chamber to 1.9 × 10⁻⁶ vacuum using a mechanical pump and a molecular pump in sequence. -3 Pa, then argon gas (50 sccm), and adjust the pressure of the vacuum chamber to 0.6 Pa.
[0138] The sputtering process uses a high-purity SiO2 target (99.9%), and pre-sputtering for 3 minutes before sputtering is performed to remove impurities from the target surface.
[0139] Then, the material was sputtered for 20 minutes under an argon gas flow and a power of 200W, followed by sputtering for 5 minutes under a mixed argon and oxygen gas flow (20 sccm) and a power of 200W, to obtain SiO2@PPy-LSDW-Al photothermal absorbing material.
[0140] 2. Assemble the evaporator
[0141] Polystyrene foam was cut into circles with a diameter of 8 cm, and the obtained SiO2@PPy-LSDW-Al photothermal absorbing material was placed on the polystyrene foam. Paper towels, absorbent cotton, filter paper, and commercial textiles were used as the supply end for bulk water and the drainage end for concentrated water. The supply end was located on both sides of the evaporator, with a width occupying 80% of the corresponding side length. The drainage ends were located on the other two sides, with a width occupying 20% of the corresponding side length, and the length of the drainage ends was greater than the length of the supply end. Evaporation performance was then tested, and the evaporation rate was 2.7 kg m³. -2 h -1 .
[0142] Example 8
[0143] 1. Preparation of SiO2@PPy / LSDW-Al photothermal absorbing material
[0144] (1) First, cut the aluminum sheet into the required size (e.g., 3*3cm), then soak it in anhydrous ethanol and sonicate it for 30 minutes. Finally, blow it dry with nitrogen to obtain a clean aluminum sheet.
[0145] (2) In an air environment, a laser marking machine (LG-20) is used to perform single-sided processing to etch an adjustable mesh microtexture surface consisting of grooves with a line spacing of 0.15 mm, a width of 0.05 mm, and a depth of 180 μm, to obtain a laser-processed aluminum sheet (LSDW-Al).
[0146] The laser parameters are set as follows: the laser beam is perpendicular to the substrate surface, the laser power is 30W, the scanning speed is 90mm / s, the line spacing is 0.15mm, the frequency is 30KHz, the scanning path is longitudinal and transverse scanning (angles are 0° and 270°), and the scanning is repeated 3 times.
[0147] (3) At 4℃, LSDW-Al was soaked in pyrrole (Py) solution for 12h to allow the microstructure of LSDW-Al to fully contact with pyrrole and allow pyrrole to be fully adsorbed on the microstructure of LSDW-Al, thus obtaining laser-processed aluminum sheet with pyrrole deposition (Py-LSDW-Al).
[0148] (4) At room temperature, a mixed solution of iodine and n-hexane with a concentration of 0.012 mmol / ml was prepared, stirred, and sonicated for 1 h to completely dissolve the iodine and obtain a homogeneous mixed solution. LSDW-Al, which was in full contact with pyrrole, was immersed in the mixed solution of iodine and n-hexane at -14°C for 48 h, and then dried in an oven at 60°C for 8 h to allow polypyrrole to adhere to the microstructure surface of LSDW-Al. Afterwards, residual iodine was removed by rinsing with anhydrous ethanol and dried at room temperature to obtain a laser-processed aluminum sheet loaded with polypyrrole (PPy-LSDW-Al).
[0149] (6) Place the PPy-LSDW-Al into the magnetron sputtering system. Using an RF power supply as the sputtering source, evacuate the sputtering chamber to 1.9 × 10⁻⁶ vacuum using a mechanical pump and a molecular pump in sequence. -3 Pa, then argon gas (50 sccm), and adjust the pressure of the vacuum chamber to 0.6 Pa.
[0150] The sputtering process uses a high-purity SiO2 target (99.9%), and pre-sputtering for 3 minutes before sputtering is performed to remove impurities from the target surface.
[0151] Then, the material was sputtered for 5 minutes under an argon gas flow and a power of 200W, followed by sputtering for 3 minutes under a mixed argon and oxygen (20 sccm) gas flow and a power of 200W, to obtain SiO2@PPy-LSDW-Al photothermal absorbing material.
[0152] 2. Assemble the evaporator
[0153] Polystyrene foam was cut into circles with a diameter of 8 cm, and the obtained SiO2@PPy-LSDW-Al photothermal absorbing material was placed on the polystyrene foam. Paper towels, absorbent cotton, filter paper, and commercial textiles were used as the supply end for bulk water and the drainage end for concentrated water. The supply end was located on both sides of the evaporator, with a width occupying 80% of the corresponding side length. The drainage ends were located on the other two sides, with a width occupying 20% of the corresponding side length, and the length of the drainage ends was greater than the length of the supply end. Evaporation performance was then tested, with an evaporation rate of 4.0 kg / m³. -2 h -1 .
[0154] Figure 1 The diagram illustrates a conventional interfacial evaporator and the induced-flow interfacial evaporator of this invention. The length of the induced-flow end is greater than that of the water supply end, allowing for a siphon effect under gravity. This maintains a low concentration of bulk water on the evaporation surface over a long period, preventing the harmful effects of salt accumulation and thus achieving highly efficient interfacial water evaporation.
[0155] like Figure 2 The morphology of each stage of the SiO2@PPy-LSDW-Al fabrication process is shown using scanning electron microscopy. Figure a1 shows the microstructure formed after laser treatment; Figure a2 illustrates the details of the grooved bonds, where aluminum sheets are etched into nanoparticles under laser treatment; Figure a3 further shows the surface of the particles. Figure b1 clearly shows the layered PPy on the microtextured surface after soaking in a mixed solution of pyrrole and iodine with n-hexane. Figure c1 shows that the arrangement of the microtexture is more ordered after magnetron sputtering.
[0156] like Figure 3The absorption spectra of clean aluminum sheets, LSDW-Al, and SiO2@PPy-LSDW-Al were measured using a UV-Vis-NIR spectrophotometer. The SiO2@PPy loading exhibited excellent light absorption (>96%).
[0157] like Figure 4 The photothermal conversion of SiO2@PPy-LSDW-Al under simulated illumination is shown in the figure. Under 0.5 cycles of simulated solar illumination, the surface temperature of SiO2@PPy-LSDW-Al reaches 79°C, and under 1 cycle of simulated solar illumination, it reaches 94°C. The surface temperature remained stable throughout the three cycles of testing, demonstrating excellent photothermal conversion capabilities.
[0158] Figure 5 The mass loss of LSDW-Al, SiO2@PPy-LSDW-Al, and SiO2@PPy-LSDW-Al under one solar simulated illumination was demonstrated. The evaporation rate of LSDW-Al was 1.61 kg m³. -2 h -1 The evaporation rate of SiO2@PPy-LSDW-Al is 3.22 kg m. -2 The evaporation rate of the SiO2@PPy-LSDW-Al-guided flow at h-1 was 4.01 kg m³. -2 h -1 The results show that the evaporation rate was greatly improved by a reasonable diversion method, which also indicates that the preparation method disclosed in this invention has excellent application prospects in the field of seawater desalination.
Claims
1. A SiO2@PPy / LSDW-Al photothermal absorbing material, characterized in that, It includes an aluminum sheet with a mesh-like microtexture on one side, a polypyrrole layer bonded to the surface of the mesh-like microtexture on the aluminum sheet, and a silicon dioxide layer loaded on the polypyrrole layer. The mesh-like microtexture is composed of multiple interlaced grooves with equal horizontal and vertical spacing, which are laser-etched. The line spacing of the horizontal and vertical grooves is 0.04-0.18 mm, the width is 0.05 mm, and the depth is 80 μm-180 μm.
2. The SiO2@PPy / LSDW-Al photothermal absorbing material according to claim 1, characterized in that, The size of the mesh microtexture is the same as that of the aluminum sheet, and the total thickness of the mesh microtexture, the polypyrrole layer, and the silicon dioxide layer does not exceed 160 μm.
3. The SiO2@PPy / LSDW-Al photothermal absorbing material according to claim 1, characterized in that, The Si atom content in SiO2@PPy / LSDW-Al photothermal absorbing materials is 0.6%-3%.
4. A method for preparing a SiO2@PPy / LSDW-Al photothermal absorbing material according to any one of claims 1-3, characterized in that, The specific steps are as follows: S1 performs single-sided laser etching on an aluminum sheet to form a mesh-like microstructure on the surface of the aluminum sheet, thus obtaining a laser-processed aluminum sheet; S2 immerses a laser-processed aluminum sheet in a pyrrole solution at 2℃-4℃ to obtain a laser-processed aluminum sheet with pyrrole deposition; S3 immersed the laser-processed aluminum sheet with pyrrole deposition in a mixed solution of iodine and n-hexane at a temperature of -14°C to -5°C, and then dried to obtain a laser-processed aluminum sheet loaded with polypyrrole. S4 sputters silicon dioxide onto the surface of a laser-processed aluminum sheet loaded with polypyrrole to obtain a laser-processed aluminum sheet loaded with silicon dioxide and polypyrrole, namely SiO2@PPy-LSDW-Al photothermal absorbing material.
5. The preparation method of SiO2@PPy / LSDW-Al photothermal absorbing material according to claim 4, characterized in that, In S1, the parameters for single-sided laser etching are set as follows: the laser beam is perpendicularly irradiated on the aluminum sheet surface, the power is 20W-30W, the scanning speed is 60mm / s-90mm / s, the line spacing is 0.04mm-0.18mm, the frequency is 20KHz-60KHz, the scanning path is longitudinal and transverse scanning, the angle is 0° and 270°, and the scanning is repeated 1 to 3 times.
6. The preparation method of SiO2@PPy / LSDW-Al photothermal absorbing material according to claim 4, characterized in that, In S2, the laser-processed aluminum sheet is immersed in a pyrrole solution for 6-12 hours.
7. The preparation method of SiO2@PPy / LSDW-Al photothermal absorbing material according to claim 4, characterized in that, In S3, the laser-processed aluminum sheet with pyrrole deposition is immersed in a mixed solution of iodine and n-hexane with a concentration of 0.006 mmol / ml-0.095 mmol / ml for 12 h-48 h, and then dried at 60℃-90℃ for 6 h-24 h.
8. The preparation method of SiO2@PPy / LSDW-Al photothermal absorbing material according to claim 4, characterized in that, In S4, the sputtered silicon dioxide uses a SiO2 target with a purity of 99.9%. The specific sputtering process is as follows: sputtering for 5 min to 40 min under an argon gas flow and a power of 150 W to 200 W, followed by sputtering for 3 min to 10 min under a mixed argon and oxygen gas flow and a power of 150 W to 200 W.
9. An interfacial evaporator, characterized in that, Including polystyrene foam, a SiO2@PPy / LSDW-Al photothermal absorbing material according to any one of claims 1-3 disposed on polystyrene foam, or a SiO2@PPy / LSDW-Al photothermal absorbing material prepared by any one of claims 4-8.
10. An interface evaporator according to claim 9, characterized in that, The SiO2@PPy / LSDW-Al photothermal absorbing material has a mesh microstructure with a supply end and a drainage end. The supply end is located on both sides of the evaporator and its width accounts for 80% of the corresponding side length. The drainage end is located on the other two sides of the evaporator and its width accounts for 20% of the corresponding side length. The length of the drainage end is greater than the length of the supply end.
Citation Information
Patent Citations
Preparation method of copper base netty photothermal conversion material
CN108914107A
Application of third biological window near-infrared light as photo-thermal conversion excitation light source
CN109539613A
